Hegemoni Budaya dalam Dinamika Dakwah di Rusia - M. Anwar Syarifuddin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2012)
Islam in Russia provided a portrait of the people who have learned from the cultural hegemony. Intimidation efforts against the spread and absorption of some of the ideas will not work, if it does not consider the effort is more persuasive. Despite these efforts can bring consequences unexpected by the authorities, but when it changes gradually raise critical awareness of the traditional Muslim society at that time, about the need to reform mindset that they hold for this, as is the case in the emergence of a reform movement of Islamic thought contained in several prominent stage. This study we will using Antonio Gramsci’s ideas which explain that the concept of hegemony by the ruling class is not merely ruled by force, but it must be done in more persuasive ways. In this persuasive ways subordinate classes are forced to learn and see themselves through the lens of the ruler, by the way thanks to the education provided.